THE DEVELOPMENT OF AL-QIRá¾¹'á¾¹T AL-SAB' LEARNING METHOD BY Qá¾¹RI'S IN LANGSA CITY - fauziah, cut; Wahid, Fatin Nabilah (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2021)
The development of al-qirÄ'Ät al-sab' is an activity that is necessarily conducted by every qirÄ'ah teacher (qÄri'). It is essential to transfer the correct readings according to the provisions recommended in Islamic law. Therefore the development of al-qirÄ'Ät al-sab' must be encouraged in the Langsa City community. The purpose of this study was to see the qirÄ'ah (qÄri') teachers in developing the al-qirÄ'Ät al-sab' learning method in Langsa City. By conducting interviews with qirÄ'Ät teachers in Langsa City and using qualitative data analysis, it shows that the qÄri's develop al-qirÄ'Ät al-sab' by holding al-qirÄ'Ät al-sab' learning in their respective homes. The methods used are bi al-ifrÄd, JibrÄ«l, TalaqqÄ«, and bi al-jamÄ' with practical learning models. The community's positive responses to al-qirÄ'Ät al-sab' learning activities help them to learn al-qirÄ'Ät al-sab,' while the negative ones are they felt prestige or embarrassed and thought it was unimportant to participate in this activity.